PSIV-17 Identification of two stem cell types derived from porcine testicular cell culture: germline stem cells and progenitor Leydig cells. (7th December 2018) - Bai, Y; Zhu, C; Feng, M; Li, J; Zhang, S
Abstract: Male germline stem cells (mGSCs) offer great promises in regenerative medicine and animal breeding because of their potential to become pluripotent stem cells (PSCs). However, the pluripotency and origin of these testis-derived stem cells remain controversial. To better characterize testis-derived stem cells, we isolated and cultured porcine mGSCs, and identified two different types of testis-derived stem cells (termed as C1 and C2) during porcine testicular cell culture, even though they shared many overlay markers. To determine which of these cell populations represent mGSCs, we compared their morphology, expression of pluripotency-associated markers, and differentiation capacity to sperm and other lineages in vitro . The C1 clusters appeared morphologically similar to the previously described mouse mGSCs, expressed pluripotency- and germ cell-associated markers, and displayed alkaline phosphatase activity. They also maintained the paternal imprinted pattern of H19 methylation and differentiated to sperms in vitro . Together, these data suggest that the C1 clusters represent the porcine mGSC population. Conversely, the C2 clusters appeared similar to the previously described porcine mGSCs and expressed Leydig cell lineage and mesenchymal cell-specific markers. They exhibited the capacity to differentiate into testosterone-producing Leydig cells, and cells of the adipogenic and osteogenic lineages in vitro, demonstrating that they are progenitor Leydig cells. Collectively, we identified two types of porcine testis-derived stem cells, mGSCs and progenitor Leydig cells. We found for the first time that, the C2, equivalent to previously claimed porcine mGSCs, are actually progenitor Leydig cells (PLCs). These findings provide new insights into the discrepancies among previous reports and future identification and analyses of testis-derived stem cells.